A comparative analysis of outcomes in patients with aneurysmal subarachnoid hemorrhage based on surgical timing - Wang, Meixue; Zhai, Jianming; Liao, Liping; Cui, Chunying; Zhu, Liangzhen; Wu, Qingjian (Frontiers in Surgery, 2025)
PurposeThe objective of this study is to investigate the optimal timing of intervention therapy for aneurysmal subarachnoid hemorrhage (aSAH). This research aims to analyze the impact of early treatment and various intervention modalities on clinical outcomes in patients presenting with aSAH.Materials and methodsPatients with aSAH were analyzed for demographics, Fisher grading, WFNS grading, and Hunt-Hess grading. The modified Rankin Scale (mRS) compared outcomes between groups receiving clamping or embolization within 12 h vs. later. Logistic regression evaluated factors affecting mRS prognosis at 3 months post-discharge.ResultsThis study included 226 patients, with 192 (85%) receiving embolization and 34 (15%) patients underwent clipping. 58 (26%) treated within 12 h of aSAH onset and 168 patients received treatment after 12 h. No significant mRS differences were found between clamping and embolization. Predictors of length of hospitalization were predicted by age, Modified Fisher classification, WFNS classification, Hunt-Hess classification, complications, and intervention time under 12 h. Early intervention <12 h significantly affected the favorable outcome of mRS (0–2) after at 3 months post-discharge; higher admission score, advanced age, and the presence of complications were associated with poor prognosis.ConclusionEarly treatment within 12 h leads to improved clinical outcomes over delayed treatment.